The sport book the sports, the rules, the tactics, the techniques (Dorling Kindersley Limited, 2016)
A guide to games, fit for everyone still buzzing from 2012, the amazing year of sport. It presents information covering all sorts of sports, from equestrian sports, athletics and gymnastics to winter sports and extreme sports.